Intratumoral and peritumoral radiomics for preoperative prediction of the efficacy of HIFU ablation for uterine fibroids based on multiparametric MRI: a multicenter study - Li, Chengwei; Liao, Hongjian; Liu, Jian; Gao, Jin (Frontiers in Oncology, 2026)
ObjectivesTo assess the predictive value of intratumoral and multiregion peritumoral radiomics based on multiparametric MRI for preoperatively predicting the efficacy of high-intensity focused ultrasound (HIFU) ablation of uterine fibroids.Materials and methodsThis retrospective study included 360 patients with uterine fibroids treated with high-intensity focused ultrasound (HIFU) at Center A (training set: N = 240; internal testing set: N = 60) and Center B (external testing set: N = 60). Patients were grouped into sufficient or insufficient ablation categories based on postoperative non-perfusion volume ratio. Intratumoral regions (TRs) were manually delineated on T2-weighted imaging (T2WI) and contrast-enhanced T1-weighted imaging (CE-T1WI). Peritumoral regions (PTRs) were generated by expanding the tumor boundary by 1 mm, 3 mm, and 5 mm. Radiomics features were extracted from TRs and PTRs on both MRI sequences. Key features for preoperative prediction were selected using t-tests, Pearson correlation, and LASSO regression. Support vector machine (SVM) models were built for TRs from T2WI and CE-T1WI, and for combined intratumoral and peritumoral regions (T-PTRs). A fusion model integrated optimal T-PTRs features from both sequences. Model performance was evaluated using the area under the receiver operating characteristic curve (AUC).ResultsThe T-PTRs radiomics models outperformed the TR models, with the T-PTRs (3 mm) model demonstrating optimal performance. The integration of T2WI and CE-T1WI further enhanced the T-PTRs model, yielding an AUC of 0.892(0.814-0.969) on the internal test set and an AUC of 0.828(0.741 - 0.915) on the external validation set.ConclusionThe predictive model based on intratumoral and peritumoral radiomics features serves as a valuable tool for predicting the therapeutic efficacy of HIFU ablation of uterine fibroids.